Chemoradiotherapy Resistance in Colorectal Cancer Cells is Mediated by Wnt/β-catenin Signaling - Emons, Georg (Mol Cancer Res, 2017)
Activation of Wnt/β-catenin signaling plays a central role in the development and progression of colorectal cancer (CRC). The Wnt-transcription factor, TCF7L2, is overexpressed in primary rectal cancers that are resistant to chemoradiotherapy (CRT) and TCF7L2 mediates resistance to CRT. However, it is unclear whether the resistance is mediated by a TCF7L2 inherent mechanism or Wnt/β-catenin signaling in general. Here, inhibition of β-catenin by siRNAs or a small molecule inhibitor (XAV-939) resulted in sensitization of CRC cells to CRT. To investigate the potential role of Wnt/β-catenin signaling in controlling therapeutic responsiveness, non-tumorigenic RPE-1 cells were stimulated with Wnt-3a, a physiological ligand of Frizzled-receptors, which increased resistance to CRT. This effect could be recapitulated by overexpression of a degradation-resistant mutant of β-catenin (S33Y), also boosting resistance of RPE-1 cells to CRT, which was, conversely, abrogated by siRNA-mediated silencing of β-catenin. Consistent with these findings, higher expression levels of active β-catenin were observed as well as increased TCF/LEF reporter activity in SW1463 cells that evolved radiation resistance due to repeated radiation treatment. Global gene expression profiling identified several altered pathways, including PPAR signaling and other metabolic pathways, associated with cellular response to radiation. In summary, aberrant activation of Wnt/β-catenin signaling not only regulates the development and progression of colorectal cancer, but also mediates resistance of rectal cancers to chemoradiotherapy. IMPLICATIONS: Targeting Wnt/β-catenin signaling or one of the downstream pathways represents a promising strategy to increase response to CRT.